Reversed association between levels of prostate specific antigen and levels of blood cadmium and urinary cadmium - Wu, Chin-Ching; Pu, Yeong S.; Wu, Hsi-Chin; Yang, Chun-Yuh; Chen, Yi-Chun (Chemosphere (Oxford), 2011)
► We recruited 295 men 50 years of age and above from a health check-up program. ► PSA levels were positively associated with the lipid levels. ► PSA levels were reversely associated with Blood cadmium and Urine Cadmium levels. Prostate cancer associated with cadmium exposure may indicate a link between prostate specific antigen (PSA) and levels of blood cadmium (BCd) and urinary cadmium (UCd). Thus, these associations were investigated. We recruited 295 men, 50 years of age and above from a health check-up program at a health center as subjects of the study. They completed a self-reported questionnaire and provided fasting samples of blood and urine for cadmium assay. The assay was performed using atomic absorption spectrophotometry. Blood samples were also collected for the assays of total cholesterol and high-density lipoprotein measures. The means of BCd and UCd increased with age and the means of all subjects were 1.19 ± 1.04 μg L −1 and 1.37 ± 1.76 μg g −1 creatinine, respectively. The PSA levels were positively associated with the lipid levels, but reversely associated with BCd and UCd levels. The multivariate logistic regression analysis showed that men with PSA ⩾ 4.0 ng mL −1 had an odds ratio (OR) of 0.4 (95% CI = 0.1–0.9) to have BCd > 0.49 μg L −1, and an OR of 0.4 (95% CI = 0.2–1.0) to have UCd > 0.45 μg g −1 creatinine. In conclusion, the PSA levels are reversely associated with BCd and UCd levels.